Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Consumer Non Cyclical Tahun 2021-2023 - Nurul Laily Barsyah; Hermi Hermi (AKUNTANSI 45, 2025)
Companies run businesses with the aim of gaining profits that can be measured by profitability. This study aims to analyze the effect of accounts receivable turnover, sales growth, inventory turnover, and cash turnover on profitability. This study is a descriptive quantitative study. This study uses panel data. The sample used in this study was 59 companies. The analysis technique used in this study is panel data regression. The results of the analysis show that (1) Accounts receivable turnover has a positive and significant effect on profitability in the consumer non-cyclical sector. (2) Sales growth does not affect profitability in the consumer non-cyclical sector. (3) Inventory turnover has a positive and significant effect on profitability in the consumer non-cyclical sector. (4) Cash turnover does not affect profitability in the consumer non-cyclical sector.